In-House Training on HOTS-based media literacy for EFL teachers in Pangandaran Regency - Sri Setyarini; Rojab Siti Rodliyah; Lulu Laela Amalia; Pupung Purnawarman; Surya Aulia Sukarman (Universitas Pendidikan Indonesia, 2026)
The rapid development of digital technology has introduced new challenges in instructional practices, particularly in relation to media literacy. Empirical conditions in Pangandaran Regency indicate that many English teachers still utilize digital media primarily as instructional support tools, with limited integration of critical analysis and Higher Order Thinking Skills (HOTS) in classroom activities. This community engagement program aimed to enhance English teachers’ understanding and professional competence in implementing a HOTS-oriented media literacy instructional model. The program employed an action research approach conducted through four stages: preparation, implementation, evaluation, and follow-up. Data were collected qualitatively through in-depth interviews, participant observation, and analysis of training documents. The participants consisted of 60 individuals, including school supervisors, principals, and junior secondary English teachers affiliated with the teachers’ professional forum (MGMP). The findings demonstrate improvements in teachers’ conceptual understanding of media literacy, shifts toward more reflective and analytical instructional strategies, and increased awareness of ethical and social dimensions of media use. The program highlights that structured HOTS-based training contributes positively to strengthening teachers’ professional competence in responding to the demands of digital-era learning environments. Abstrak Perkembangan teknologi digital yang pesat menghadirkan tantangan baru dalam praktik pembelajaran, khususnya terkait literasi media. Kondisi empiris di Kabupaten Pangandaran menunjukkan bahwa sebagian besar guru Bahasa Inggris masih memanfaatkan media digital sebagai alat bantu penyampaian materi, dengan integrasi analisis kritis dan keterampilan berpikir tingkat tinggi (HOTS) yang masih terbatas dalam kegiatan pembelajaran. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman dan kompetensi profesional guru Bahasa Inggris dalam menerapkan model pembelajaran literasi media berbasis HOTS. Program dilaksanakan menggunakan pendekatan kaji tindak melalui empat tahap, yaitu persiapan, pelaksanaan, evaluasi, dan tindak lanjut. Pengumpulan data dilakukan secara kualitatif melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen pelatihan. Partisipan kegiatan berjumlah 60 orang yang terdiri atas pengawas sekolah, kepala sekolah, dan guru Bahasa Inggris tingkat SMP yang tergabung dalam MGMP. Hasil kegiatan menunjukkan adanya peningkatan pemahaman konseptual guru terhadap literasi media, perubahan strategi pembelajaran yang lebih reflektif dan analitis, serta meningkatnya kesadaran terhadap dimensi etika dan sosial dalam penggunaan media. Program ini menegaskan bahwa pelatihan terstruktur berbasis HOTS berkontribusi positif dalam memperkuat kompetensi profesional guru dalam menghadapi tuntutan pembelajaran di era digital. Kata Kunci: HOTS; in-house training; kompetensi profesional guru; literasi media.